2017
DOI: 10.1139/cjpp-2016-0634
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of endothelial-to-mesenchymal transition in cardiac fibrosis: role of myocardin-related transcription factor A and activating transcription factor 3

Abstract: The etiology of cardiac fibrogenesis is quite diverse, but a common feature is the presence of activated fibroblasts. Experimental evidence suggests that a subset of cardiac fibroblasts is derived via transition of vascular endothelial cells into fibroblasts by endothelial-to-mesenchymal transition (EndMT). During EndMT, endothelial cells lose their endothelial characteristics and acquire a mesenchymal phenotype. Molecular mechanisms and the transcriptional mediators controlling EndMT in heart during developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 85 publications
2
13
0
Order By: Relevance
“…Furthermore, Foxm1 bound to and increased the promoter activity of the Snail gene, which encodes a critical transcriptional regulator of the EndMT [27]. ATF-3 responds to TGF-β and controls the expression of the primary epithelial-to-mesenchymal transition markers, Snail, Slug, and Twist [28]. These three transcription factors are thought to be associated with TGF-β-induced EndMT.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Foxm1 bound to and increased the promoter activity of the Snail gene, which encodes a critical transcriptional regulator of the EndMT [27]. ATF-3 responds to TGF-β and controls the expression of the primary epithelial-to-mesenchymal transition markers, Snail, Slug, and Twist [28]. These three transcription factors are thought to be associated with TGF-β-induced EndMT.…”
Section: Discussionmentioning
confidence: 99%
“…miR-222 overexpression ameliorated cardiac fibrosis Fibrosis is a process in which fibroblasts are overactivated and extracellular matrix proteins are deposited, leading to cardiac remodeling and dysfunction (Frangogiannis, 2019). Fibroblasts are the major collagen-producing cells, and continuous stimulation under pathological conditions leads to their overactivation and the overproduction of collagen (Sharma, Dogra, Saikia, & Khullar, 2017). A recent study reported that in aortic stenosis patients, miRNA-222 levels were negatively related with myocardial fibrosis (Verjans et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of ischemia-reperfusion injury, overexpression of PRR aggravated renal inflammation and fibrotic lesions by amplifying Wnt/ β -catenin signaling rather than relying on Ang II [32]. In postmyocardial infarct hearts, PRR increased myocardial fibrosis and worsened cardiac function, and these effects did not depend on Ang II [34].…”
Section: Discussionmentioning
confidence: 99%